«Den sletteste, den nedrigste og uretfærdigste Embeds Mand» Om prosessen mot byfogd og politimester i Christiansand Mauritz Antonius Schweder - Heivoll, Geir (Nordisk Tidsskrift for Kriminalvidenskab, 2020)
Abstract The first Norwegian Chiefs of Police were appointed in the four main cities during the latter part of the 1600s. The first office was established in Trondheim in 1686, then Bergen in 1692, Christiania in 1744, and finally Christiansand in 1767. This article deals with the establishment of the police in Christiansand, when Christian VII appointed Mauritz Antonius Schweder Chief of Police in the city. Schweder had already been appointed as a bailiff in Christiansand in 1764, and from 1767 he was both bailiff and Chief of Police. But Schweder’s time in office was a turbulent one, and the conflict surrounding his office escalated so much as to finally end in the retraction of his professional appointment by the Supreme Court in Copenhagen. This article focuses on the trial against Schweder: the many accusations against him, his defense, and the ruling of the Supreme Court, thereby shedding light on a lesser known part of the legal history of the early Norwegian Police.